Saberes em construção de uma professora que pesquisa a própria prática. - Sudan, Daniela Cássia (2005)
This research, with qualitative characteristics, involves an autobiographic study inserted into a perspective of continuous formation of the teacher, by means of reflexive practice. It aims at identifying and analyzing: i) the knowledge base which was recognized,transformed and produced by the teacher as researcher; and, ii) the contributions offered by certain interlocutors linked to the educational universe, to consolidate part of this knowledge and to promote reflexive processes. The main theory references which orientated this research were the works of Zeichner (1992, 1993, 1998); Schön (2000), Tardif (1991, 2000, 2002) and Nóvoa (2000). On the other hand, the method used was based on an autobiographic proposal and on interpretative theories of documents of the teacher as researcher. The main activities and procedures include filming the classes, day-by-day written records, and audio record of the reflexive meetings with the interlocutors. During the work, it was possible to observe that the teachers knowledge under development mostly derivate from the background influence generated by family, school and university lives, by the personal/professional experiences in schools, and by the interactions of the teacher and a number of interlocutors she met while working, both in formal training activities and during the research. The teacher developed her practice by creatively exploring the traditional teaching places, bringing up contents of attitude, procedures and concepts, valorizing the discussion and stimulating the interactions and the collective work of the students. The conduction and sustenance of the teachinglearning process is characterized by an articulated sequence of activities, by the development of the didactic contract and by the evaluation of the discipline and progression of learning. Some dilemmas are typical of her professional life, such as the handling of the subject in school time and the development of a teaching technique which consider the reality of the students. The division of the teaching experience allowed the objectivity of several implicit theories. The unbalancing situations caused by the interlocutors created an intense involvement of the teacher with the reflexive process about practice, leading to some discoveries and to the revision of the understanding of teaching. Moreover, they motivated the overcome of some pedagogical illusions and of an individualist perspective of the teaching activity. The teacher-researcher could understand that many of her dilemmas are especially constituted of institutional problems of the Brazilian educational system, which needs more than just the personal reflection of the teachers. This work may offer some clues that the promotion of researches by high school teachers contribute to an increase of the professional development, to the appropriation and improvement of their knowledge base, to a perception of the gaps to be reviewed in a continued process, and to the refining of the decision about becoming a teacher.